Research projects in human genetics in Switzerland: analysis of research protocols submitted to cantonal ethics committees in 2018 (Swiss Medical Weekly, 2021)
AIM OF THE STUDY This analysis provides a full national overview of genetic research dossiers pertaining to clinical and nonclinical trials, and to further-use research projects submitted for approval to ethics committees in Switzerland in 2018. It addresses the research type, medical field, number of individuals or datasets involved, diagnostic laboratories and data privacy, as well as the procedures foreseen for obtaining consent, communicating results, and dealing with excess data and incidental findings. The analysis results should constitute a basis for future discussions surrounding regulatory and ethical procedures that govern genetic investigations in biomedical research in Switzerland. METHODS All research dossiers approved by ethics committees in 2018 were screened for genetic investigations. A sample of 122 dossiers were analysed in depth, with regards to the frequency of genetic investigations, overall purpose and number of human beings or datasets included, in addition to the diagnostic categories and methodologies that were employed. The number of genes, biosample storage conditions and laboratory types concerned were also recorded. The processes for obtaining informed consent, communicating the results to the participants and predetermined principles for handling incidental findings were analysed. RESULTS Genetic investigations were retrieved from 9% of all research applications. The focus of most clinical trials was pharmacogenetics, whereas research projects of further use of data and/or biological material were mostly investigator-initiated and focused on basic genetic research and multiple gene analysis. Overall, big datasets (i.e., more than 100 or even 1000 sets) were included, especially in further-use research projects. Nongermline somatic genetic investigations were a large research field in oncology (56%), whereas genetic germline testing was mostly performed in neurology or psychiatry. In most cases, numerous genes were analysed. Modern sequencing techniques were employed, rendering excess genetic information nearly inevitable. Information regarding the storage of genetic data was mostly lacking, whereas information regarding the biosample storage was mostly provided. Data protection and informed consent procedures aligned with legal, regulatory and ethical standards. Procedures for communicating genetic analysis results and incidental findings to research participants were not predetermined in most research protocols, and they were handled differently from informed consent and general consent forms. CONCLUSIONS This study overviewed the key dimensions of regulatory and ethical assessments pertaining to genetic investigations that are performed on human beings as part of research projects in Switzerland. The data’s potential impact to shape the Federal Act on Human Genetic Testing and the Human Research Act in the future is also discussed. A direct transfer of standards for quality, consultation and communication of genetic testing within clinical genetic routines to genetic testing of human beings in the research context is neither required nor appropriate. It would bear a high risk of excluding patients and the Swiss health system from seminal innovations in medicine and life-science research.